Training and Assistance in Village Population Databases for Sea Dua and Sea Mitra Officials - Mosey, Handy Indra Regain; Mananohas, Mans Lumiu; Takaendengan, Mahardika Inra; Lapihu, Dodisutarma (Universitas Teknokrat Indonesia, 2025)
The primary objective of modern technological advancements is to enhance efficiency in tasks and services, particularly in administrative operations and office systems. However, the integration of advanced technology, specifically in database applications and information systems, has become increasingly critical for village services. The limited technological proficiency among village officials, particularly the village secretaries, has hindered the effectiveness of population data management in Sea Dua and Sea Mitra Villages. Therefore, training in the implementation of population databases is essential for improving the performance of the local government officials in these villages. This Community Service Program (PKM) aims to provide comprehensive training in the use of population database technology and to offer ongoing support to village staff in adopting modern technologies, ultimately enhancing the efficiency and effectiveness of administrative services in Sea Dua and Sea Mitra Villages, Pineleng Subdistrict, Minahasa Regency.